The choir lectern of Angra Cathedral (Terceira Island, Azores) - Henriques, Luís (2024)
The Cathedral of Angra do Heroísmo (Terceira Island, Azores) has a choir lectern that was in use throughout the nineteenth century until around the 1960s. This lectern once belonged to the town’s Franciscan convent of São Francisco and was extant at its church’s high choir until the 1830s when it was transferred to the Cathedral following the extinction of the religious orders in the Portuguese territory. This text examines the musical context of this object from its place of origin to the actual location.